Comparison of Manual Tools, Ultrasonic and Erbium-Doped Yttrium Aluminum Garnet (Er:YAG) Laser on the Debridement Effect of the Surface of the Root of Teeth Suffering from Periodontitis - Foroutan, Tahereh; Amid, Reza; Karimi, Mohammad Reza (Journal of Lasers in Medical Sciences, 2013)
Introduction: Periodontal diseases are considered as some of the most common reasons of teeth loss, which occur due to the aggregation of microbial plaque and other precipitations on the dental surfaces. In this study, the scaling effect using manual tools, ultrasonic machine and Erbium-Doped Yttrium Aluminum Garnet (Er:YAG)laser on the connection of the human gums connective tissue cells on the root surface of the teeth suffering from severe periodontitis will be compared. Methods: After removal of the big precipitations with manual tools, Er:YAG laser light emission of Photona machine is used with respect to the following characteristics: wavelength: 2940μm, each pulse: 100mJ, frequency: 10 pulse/sec, optic fiber with cross section 0.5x1.65mm, fiber tip angle with root surface: 15-20 degrees with non-contact mode, 1.5mm farther than the root surface and pulse duration 230 very short. The gingival fibroblast cellular was incubated as a sample of the human gums connective tissue cells under 37C. These cells were departed from the culture medium after the cellular reproduction in the third passage.On the 3rd day after incubation, the gingival fibroblast cells morphology was studied by Scanning Electron Microscopy (SEM). Results: The results of SEM images in the present study indicated the spread fibroblast cells with philopodia were found in all of 5 groups; untreated healthy group (control), untreated group suffering from periodontitis, the scaling effect using manual tools (Scaled Gracey), ultrasonic machine and Er:YAG laser. There is a meaningful difference among the three treatment groups (P<0.001) in the numbers of the fibroblast cells, while all the four treated groups had a meaningful difference with the positive control group (P < 0.001). Conclusion: The present study indicated that although various dental surfaces cleaning methods may be different in other aspects, but are similar concerning the fibroblasts morphology. Also in addition to power, laser emission time may also be effective in the cells morphology results.